Migration and social economic effect (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The trial aims to determine the socioeconomic problems that are generated by the migrations of Nicaraguans. We have designed a desk study, based on some theories of economists thinkers. This case was investigated on conflicts generated by the migration of Nicaraguan citizens, usually middle-class low to developing countries also take into account both quantitative and qualitative variables, through this research data concerning obtained the demographic and socioeconomic, important to consider in the study of migration issues. Nicaraguan migration is due to the poor condition of survival experienced by the population of low income, lack of resources, dysfunctional families, informal employment, lack of professional education. As a result of the research presented, we can conclude that there are different reasons why thousands of Nicaraguans migrate every year. However this essay analyzes the migration from a general point of view the problem for which traverse the poor families who have a relative abroad. DOI: http://dx.doi.org/10.5377/reice.v2i4.1731 REICE Vol. 2, No. 4, julio-diciembre 2014: 149-158
Keywords: migration; economic development; demography